Heart disease : a textbook of cardiovascular medicine - Braunwald, Eugene (W.B. Saunders, 1997)
The Fifth Edition of the definitive reference on heart disease -- has been assiduously revised and updated Dr. Braunwald has added 23 new chapters and 22 renowned new contributors to bring readers the state of the art in the field of cardiology. From examination and circulatory function to diseases of the heart and broader perspectives on heart disease and cardiologic practice, this classic resource remains authoritative, user-friendly, and complete.
Keywords: nemoci srdce; kardiologie; angiologie; Heart Diseases